The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.31744/einstein_journal/2022rw6155
|View full text |Cite
|
Sign up to set email alerts
|

Metformin versus glyburide in treatment and control of gestational diabetes mellitus: a systematic review with meta-analysis

Abstract: Objective: To compare the major outcomes of use of metformin and glyburide in treatment of gestational diabetes mellitus. Methods: Studies published in English, in the last 10 years, in the databases MEDLINE ® , SciELO, LILACS and Cochrane Library were analyzed, and randomized controlled trials were selected. Health Sciences Descriptors were used to compose the search phrase, and the keywords "Gestational diabetes", "Glyburide", "Metformin" and their variations were searched in the Medical Subject Headings. PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Like metformin, glyburide can cross the placenta and potentially affect a growing fetus [43]. Multiple meta-analyses sought to compare the safety and efficacy of glyburide with metformin therapy in pregnancy, as these are the only oral diabetic agents currently available for this population and are commonly prescribed in combination with insulin [100][101][102][103]. Glyburide is about equal to metformin in its contribution to glycemic control in pregnant women with diabetes.…”
Section: Pharmacotherapy In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Like metformin, glyburide can cross the placenta and potentially affect a growing fetus [43]. Multiple meta-analyses sought to compare the safety and efficacy of glyburide with metformin therapy in pregnancy, as these are the only oral diabetic agents currently available for this population and are commonly prescribed in combination with insulin [100][101][102][103]. Glyburide is about equal to metformin in its contribution to glycemic control in pregnant women with diabetes.…”
Section: Pharmacotherapy In Pregnancymentioning
confidence: 99%
“…A meta-analysis that compared glyburide and metformin in patients with GDM found no difference in fasting blood glucose (p = 0.821), postprandial blood glucose (p = 0.217) and birth weight (p = 0.194) between the interventions. However, glyburide is associated with more adverse effects, including maternal weight gain, macrosomia, neonatal hypoglycemia, and neonatal disease [100]. When safety and efficacy are evaluated, glyburide seems to be inferior to metformin in the treatment of diabetes in pregnancy because it has more adverse effects and only comparable efficacy, with a lack of long-term data on its effects on the fetus.…”
Section: Pharmacotherapy In Pregnancymentioning
confidence: 99%
“…Current studies have demonstrated that the occurrence and development of GDM is influenced by multiple factors, among which genetic, metabolic and environmental factors are important in the pathogenesis of GDM (5). Currently, we recommend dietary modification and increasing appropriate physical activity to improve gestational diabetes, and when basic methods cannot control blood glucose, insulin therapy (6) or oral hypoglycemic agents, mainly metformin and glibenclamide (7), are mostly used. The majority of current studies have focused on hypoglycemic approaches to treat GDM.…”
Section: Introductionmentioning
confidence: 99%
“…The basic methods of treating GDM include an appropriate diet and increased physical activity, and when these are inadequate, pharmacotherapy, usually insulin therapy, is used. In developing countries, such as Brazil, oral hypoglycemic agents are also used, mainly metformin and glibenclamide (glyburide) [ 10 ]. The prevention and appropriate treatment of GDM are needed to reduce the morbidity, complications and economic effects of GDM that affect society, households and individuals.…”
Section: Introductionmentioning
confidence: 99%